Pengaruh Strategi Manajemen Rantai Pasok Terhadap Kinerja Operasional Pada Usaha Mikro Kecil Dan Menengah - Jennifer Victoria Astari Haryanto; Wahyuningsih Santosa (Sains: Jurnal Manajemen dan Bisnis, 2022)
Micro, Small and Medium Enterprises play a very large role for the Indonesian economy and indirectly support the Indonesian economy. Therefore, this study aims to identify whether supply chain management strategies have an influence on operational performance in Micro, Small and Medium Enterprises, by collecting data using a questionnaire addressed to 151 respondents. Then the test was carried out using the Structural Equation Method (SEM). The results obtained are that not all supply chain management strategies used affect the operational performance of Micro, Small and Medium Enterprises, of the five supply chain management strategies used, there is one strategy that has no effect on the operational performance of a business.